Concentrating solar power in South Africa - a comparison between parabolic trough and power tower technologies with molten salt as heat transfer fluid - Poole, Ian Vincent (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.